HUBUNGAN MASA KERJA DAN PENGGUNAAN APD DENGAN GANGGUAN FUNGSI PARU PADA PENYAPU JALAN DI RUAS JALAN TINGGI PENCEMARAN KOTA SEMARANG - Sholihati, Nina; Suhartono, Suhartono; Dewanti, Niki Astorina Yunita (Jurnal Kesehatan Masyarakat (e-Journal), 2017)
Respiratory illness is the third most common cause of death in the world, following heart problems and cancer. In 2008, the incidence of mortality reached 135.5 / 100,000 deaths. One of the groups at risk of air pollution is street sweepers in Setiabudi Street, Walisongo Street, and Kaligawe Street of Semarang City which have high dust level. The purpose of this study is to know the prevalence of lung function disorders as well as the relationship between the working duration and the use of PPE with lung function disorders on respondents. This research is a kind of quantitative research with Cross Sectional study design. The sample of this research is all of the street sweepers in Setiabudi Street, Walisongo Street, and Kaligawe Street as many as 31 people. The results of this study showed 5 respondents have lung function disorder (16.1%). The result of statistics analysis showed that there is no correlation between working duration with pulmonary function disorder with p value %FVC = 0,082 and p value %FEV1 = 0,595. While there is no correlation between the use of PPE with pulmonary function disorder with p value of 0,317 (PR = 3,375; 95% CI = 0,469-24,287). The longer the working period, the lower the lung capacity of the street sweeper. Suggestions in this study are expected to be information and reference for the Environment Agency and related parties in safety and health planning of street sweepers, especially on the lungs of workers.